2022
DOI: 10.5713/ab.21.0318
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus amyloliquefaciens and Saccharomyces cerevisiae feed supplements improve growth performance and gut mucosal architecture with modulations on cecal microbiota in red-feathered native chickens

Abstract: Title of the manuscript: Bacillus amyloliquefaciens and Saccharomyces cerevisiae feed supplements improve growth performance and gut mucosal architecture with modulations on cecal microbiota in red-feathered native chickens ABSTRACT Objective: The aim of study was to investigate the effects of in-feed supplementation of Bacillus amyloliquefaciens (BA) and Saccharomyces cerevisiae (SC) on growth performance, gut integrity and microbiota modulations in red-feathered native chickens (RFCs).Methods: A total of 18,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…The supplement of SP and VE improved growth performance of Guinea fowls including body weights and feed conversion ratio in this study. It was in line with the study of Merati et al (2021), Jabbar et al (2021 and Lee et al (2022). This could be explained that the supplementation of SP or VE improving antibody resistance and stimulating feed digestion and nutrient absorption, resulted in increasing weight gain.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The supplement of SP and VE improved growth performance of Guinea fowls including body weights and feed conversion ratio in this study. It was in line with the study of Merati et al (2021), Jabbar et al (2021 and Lee et al (2022). This could be explained that the supplementation of SP or VE improving antibody resistance and stimulating feed digestion and nutrient absorption, resulted in increasing weight gain.…”
Section: Resultssupporting
confidence: 86%
“…The Saccharomyces cerevisiae absorbs oxygen in the digestive tracts supporting the development of beneficial bacteria, while limiting the growth of the harmful ones as a result to improve the health and performace of animals. As the same ways of using microorganisms, Lee et al (2022) recorded that Saccharomyces cerevisiae and Bacillus amyloliquefaciensin-feed supplementation improve growth rate and modulated the cecal microbiota. The supplement of enzymes has also brought positive effects on growth performance and microbiota ( Jabbar et al, 2021).…”
mentioning
confidence: 96%
“…Prior research has documented that dietary supplementation with B. subtilis probiotics did not affect broiler growth performance during the d 1 to 21 period; instead, it increased average daily gain (ADG) and feed intake, as well as decreased FCR from day 22 to day 42 compared to the control group [ 15 ]. In contrast, other studies reported that Bacillus amyloliquefaciens and Saccharomyces cerevisiae feed supplements did not significantly enhance growth performance at the age of nine weeks, but increased growth performance at the age of 11 weeks in red-feathered native chickens [ 16 ]. However, no significant changes in body weight or ADG were observed herein.…”
Section: Discussionmentioning
confidence: 95%
“…Enhanced biosynthesis of peptidoglycan may increase the abundance of lactic acid bacteria populations in the gut, partially facilitating the growth benefits. ( Lee et al, 2022 ). Peptidoglycan can exert anti-inflammatory roles in the intestinal epithelia cells through the peptidoglycan recognition protein ( Zenhom et al, 2012 ), indicating the anti-inflammatory roles of seaweed.…”
Section: Discussionmentioning
confidence: 99%